Surface Lipids Isolated from the Leaves of Boscia salicifolia Oliv. - Angelika Walter; Urs Séquin (CHIMIA)
The surface lipids of the leaves of Boscia salicifolia Oliv. were investigated by means of gas chromatography/mass spectrometry. The hydrocarbon fraction contained n-alkanes (n-C20H42 to n-C33H68) with heptacosane as the main component. Octacosanol proved to be the major constituent of the fraction of the primary n-alcohols; the aldehyde fraction consisted of saturated n-aldehydes, octacosanal being the main compound here. Furthermore, the phytosterols lupeol, taraxasterol, stigmasterol, and β-sitosterol were isolated.